Integrasi Sistem Pendidikan Salaf dan Khalaf di Pondok Pesantren Bilingual An-Nahdliyah 5 Gombong - Anggun Lutfiani; Fikria Najitama; Agus Nur Soleh (IAINU Kebumen, 2023)
The research objectives are: (1) to analyze the curriculum system, and learning methods in the integration of salaf and khalaf at the Bilingual Islamic Boarding School An-Nahdliyah 5 Gombong and (2) to analyze the implementation of the integration of the salaf and khalaf education systems at the An-Nahdliyah 5 Gombong Bilingual Islamic Boarding School. This research is in the form of field research, using qualitative methods. Data collection techniques used observation, interviews, and documentation. The subjects of this study were the Principals of the Islamic Boarding School, Asatidz, and the students of the An-Nahdliyah 5 Gombong Bilingual Islamic Boarding School. Based on the results of the study, it can be concluded that: (1) The curriculum used by the Bilingual Islamic Boarding School An-Nahdliyah 5 Gombong is a salaf curriculum with classical books as the main material and by mixing and matching the khalaf method, namely classical as a learning method and (2) the implementation of the integration of the salaf and khalaf education systems at the An-Nahdliyah 5 Gombong Bilingual Islamic Boarding School, seen by the existence of various integrated things and activities, such as: (a) time allocation; (b) skills and technology activities; (c) managerial leadership; (d) entrepreneurial students; (e) integration of educators.